Pengaruh Pengeluaran Pemerintah Di Sektor Pendidikan, Kesehatan, Perumahan Dan Fasilitas Umum Terhadap Indeks Pembangunan Manusia Di Provinsi Sumatera Barat - Aprillia Wahyuni; Syamsul Amar B (Universitas Negeri Padang, 2023)
This study intends to examine the effect of government budget allocation on the allocation of education, health, housing, public facilities on HDI in West Sumatra Province. The data used in this study is secondary data from 2011 to 2020. This study uses panel data analysis techniques. The results of the analysis prove that the allocation of government costs in the allocation of education, health, housing and public facilities has a positive and significant impact on human development in West Sumatra Province. Meanwhile, the simultaneous allocation of government spending in the education, health, housing and public facilities sectors has a significant effect on the human development index in the Regency/City of West Sumatra Province.